Waste : a handbook for management - Letcher, T. M. (Trevor M.); Vallero, Daniel A. (Burlington, MA : Academic Press, 2011)
"Preface Waste: A Handbook of Waste Management is designed to be a resource for the designer, practitioner, researcher, teacher and student. Waste is one of those entities which is defined by everyone, but not truly and completely understood by anyone. The scientist, engineer and consumer each define waste correctly, yet differently. The overriding challenge for the authors was to provide some uniformity, yet allow for the diversity of the various aspects of waste in this handbook. After all, a handbook is often the beginning of the search for information, certainly not the end. We have borrowed from all scientific disciplines, and a few humanities, to arrive at a balanced resource. And, indeed, balance is the key to environmental science and engineering"--
Machine generated contents note: 1. A History of Waste Management 2. Green Engineering and Sustainable Design Aspects of Waste Management3. Waste Regulations with special emphasis to the USA 4. Waste Collection 5. Mine Waste: A Brief Overview of Origins, Quantities and Methods of Storage6. Metal Waste 7. Radioactive Waste Management8. Municipal Waste Management 9. Waste Water: Reuse of Oriented Wastewater -- Low- and High-Tech Approaches for Urban Areas10. Recovered Paper 11. Glass Waste12. Textile Waste13. Chemicals in Waste: Household Hazardous Waste 14. Reusing Non-hazardous Industrial Waste across Business Clusters15. Construction Waste 1. 16.Thermal Waste Treatment 16. Plastic solid waste (PSW) and thermo-chemical treatment 17. Air pollution (including pollution due to Coal and Oil Burning, Cement Making and Automobile exhaust pollution 18. Ocean pollution19. Electronic Waste 20. Tyres21. Battery Waste22. Medical waste 23. Agricultural Waste and Pollution 24. Military waste25. Space waste26. Hazardous Wastes 27. Land Pollution 28. Thermal Pollution29. Landfills, Yesterday, Today and Tomorrow 30. Pollution Management and Responsible Care31. Risk Assessment, Management and Accountability Epilogue Index.
Includes bibliographical references and index.
Keywords: Factory and trade waste -- Handbooks, manuals, etc; Refuse and refuse disposal -- Handbooks, manuals, etc